The Onlife Manifesto: Being Human in a Hyperconnected Era (2015)
On the 8th of February 2013, The Onlife Manifesto1 was released at an inaugural event held in Brussels by DG Connect, the European Commission Directorate Gen- eral for Communications Networks, Content & Technology.2 The Manifesto was the outcome of the work of a group of scholars, organised by DG Connect, which I had the privilege to chair: Stefana Broadbent, Nicole Dewandre, Charles Ess, Jean-Gabriel Ganascia, Mireille Hildebrandt, Yiannis Laouris, Claire Lobet-Maris, Sarah Oates, Ugo Pagallo, Judith Simon, May Thors- eth, and Peter-Paul Verbeek. During the previous year, we had worked quite intensely on a project entitled The Onlife Initiative: concept reengineering for rethinking societal concerns in the digital transition. 3 We decided to adopt the neologism “onlife” that I had coined in the past in order to refer to the new experience of a hyperconnected reality within which it is no longer sensible to ask whether one may be online or offline. Also thanks to a series of workshops organised by DG Connect, we had investigated the challenges brought about by the new digital technologies. We had debated the impact that ICTs are having on human life, and hence how one may re-engineer key concepts—such as attention, ownership, privacy, and responsibility—that are essential in order to gain the relevant and adequate framework within which our onlife experience may be understood and improved.